Multifunctional Beta‐ Cyclodextrin‐Modified Selenium Hybrid Hollow Mesoporous Silica Nanospheres for Mitochondrial Targeted Carbon Monoxide Delivery - Zhou, Junyi; Lian, Yating; Wang, Hanzhang; Lu, Bin; Zheng, Xue; Lai, Jieying; Wang, Fen; Guo, Shuang‐Zhuang; Zhang, Li‐Ming (Small (Weinheim an der Bergstrasse, Germany), 2025)
Carbon monoxide (CO) gas therapy has recently emerged as a promising strategy for cancer treatment. However, the uncontrolled release of CO and challenges in accumulating it at tumor sites have limited its therapeutic efficacy. In this work, a stepwise targeted delivery and a controlled release strategy for CO gas is proposed. By encapsulating a mitochondria‐targeting CO prodrug (TPP‐CORM) in biodegradable hybrid hollow mesoporous silica nanoparticles and coating tumor‐targeting ligands on the surface of the mesoporous silica via host–guest interactions, targeted delivery of CO gas from tumor tissue to tumor cells and ultimately to mitochondria is achieved. After safely and efficiently delivering CO to the mitochondria of tumor cells, CO induces mitochondrial damage, leading to metabolic disruption, a reduction in adenosine triphosphate (ATP) levels, mitochondrial membrane depolarization (ΔΨ reduction), and subsequently, the induction of apoptosis in tumor cells. This stepwise targeted CO delivery strategy provides a novel approach for targeted tumor therapy using CO gas.